State anxiety and positive affect among modern digital native generations compared to earlier Polish generations - Barbara Gawda; Kalina Kosacka (Journal of Modern Science, 2025)
Objectives We aimed to compare state anxiety and positive affect in people from the Polish digital native generations and older generations as some researchers suggest that experiencing fear and positive emotions in digital generations is higher and associated with excessive use of social media.